A small shrine placed to the right facing the garbhagriha - Temples of India Project Team (Jio Institute, 2024)
A small shrine, possibly a newer construction, is placed off-centred to the right facing the garbhagriha. Further steps lead to the third level, on a projected platform. The upper part made of concrete is a later addition. The structure has arched openings on the west, east, and north sides with a rectangular entrance inside an arched niche (seen here) on the south side. Instead of the traditional shikhara, the temple was reconstructed with a concrete dome by the Archaeology Department of the erstwhile Jaipur State in the 1940s.